The effect of fluticasone furoate/umeclidinium in adult patients with asthma: A randomized, dose-ranging study. Issue 1 (January 2015) - Lee, Laurie A.; Yang, Shuying; Kerwin, Edward; Trivedi, Roopa; Edwards, Lisa D.; Pascoe, Steven
Summary Background We evaluated the dose–response of umeclidinium (UMEC; a long-acting muscarinic antagonist) combined with fluticasone furoate (FF; an inhaled corticosteroid [ICS]) in patients with asthma. Methods In a double-blind, three-period crossover study, 421 subjects (symptomatic on ICS), were randomized to a sequence of three of seven treatments: FF 100 mcg alone, FF 100 mcg combined with UMEC (15.6, 31.25, 62.5, 125, or 250 mcg), or vilanterol 25 mcg (a long-acting β-agonist), inhaled once-daily for 14 days (12–14-day washout). Trough forced expiratory volume in one second (FEV1), peak expiratory flow (PEF), and safety were assessed. Results Period baseline was a significant covariate, indicating a potential carryover effect between treatment periods. Across all treatment periods, trough FEV1 improved with FF/UMEC 125 and 250 versus FF (treatment difference 0.055 L [both doses]; p = 0.018). FF/UMEC increased morning (15.9–22.9 L/min) and evening (16.2–28.8 L/min) PEF versus FF. As intended assessments were confounded, post hoc Period 1 data analyses were performed, demonstrating significant increases in trough FEV1 with FF/UMEC 31.25, 62.5, and 250 versus FF. Trough FEV1 improvements with FF/UMEC were greater in subjects with fixed (0.095–0.304 L) versus non-fixed (−0.084 to 0.041 L) obstruction. The incidence of on-treatment adverse events was 13–25% across groups. No treatment-related effects on laboratory parameters were reported. Conclusion FF/UMEC may be a viable treatment for patients with asthma symptomatic on ICS; benefit may be most prominent in those with fixed obstruction. The carryover effect suggests future UMEC studies should use an alternative design. ClinicalTrials.gov: NCT01573624.